Sustainability of national parks and game reserves during the Covid-19 pandemic in Kenya - Janet C. Kimeto; Kezia Herman Mkwizu (School of Tourism, Universitas Ciputra Surabaya, 2023)
This paper is to explore sustainability of national parks and game reserves in Kenya. Objectives are to examine the responsibility of tourism stakeholders in sustainability of national parks and game reserves during the Covid-19; explore the benefit and cost of tourism of parks and game reserves during the Covid-19; and explore the mitigating measures by tourism stakeholders on issues affecting wildlife in parks and game reserves during the Covid-19 pandemic. The methodology is based on a literature review method by deploying a systematic literature review. The findings indicated that as much as tourism is globally seen as an income generator and foreign exchange earner but was worst hit by the pandemic. If the effects of the pandemic are not mitigated early, then the effects are harmful to the resources and environment. Tourism stakeholders should ensure posterity and fame of parks and game reserves are sustained. This paper provides information on the responsibilities of tourism stakeholders in the sustainability of parks and game reserves in Kenya as a tourism destination. The outcome of this paper implies that the tourism stakeholders may look into ways of mitigating the negative effects of tourism in the Covid-19 to ensure sustainability in the post- Covid -19 pandemic.